Integrasi Pemasaran Storytelling dan Konten Edukasi mengenai Spa Bayi pada Platform Media Sosial UMK IKKI Baby and Kids SPA Surabaya - Fernandi Fernandi; Ayun Maduwinarti (Jurnal Manajemen dan Ekonomi Kreatif, 2025)
This community service programme's objective is to integrate storytelling marketing and educational content marketing in promoting baby spa services at MSEs IKKI Baby and Kids Spa Surabaya. In light of the increasing demand for baby spa services, MSEs must adopt effective marketing strategies through social media platforms. The service activity was conducted over a period of one month and involved MSE owners and employees. The methods employed encompass observation, education, and social media development, in collaboration with IKKI Baby and Kids Spa Surabaya MSEs through the Wirausaha Merdeka (WMK) Batch 3 program of Universitas 17 Agustus 1945 Surabaya. The findings of the community service demonstrate that the integration of a storytelling marketing strategy with educational content can enhance the engagement rate by 40% within a one-month period. Furthermore, owners and employees reported an increase in confidence, and a renewed sense of purpose in the management of digital content, accompanied by a heightened awareness of the significance of delivering pertinent and engaging information to consumers. This community service initiative has yielded substantial contributions to the enhancement of digital marketing literacy among MSEs, underscoring the considerable potential of social media marketing in reaching a more extensive audience.